The transfer function of human body on vertical sinusoidal vibration - LIU, Jian Zhong; KUBO, Mitsunori; TERAUCHI, Fumio; AOKI, Hiroyuki (Ningen kogaku. The Japanese journal of ergonomics, 1996)
Vibration transfer function of human body is examined with transmissibility and phase difference in this study. The transmissibility is expressed by the ratio between the vibration acceleration on the body and the vertical vibration acceleration on the vibration table, and the phase difference by the phase angle between the vibration accelerations on the body and the table. The subjects are five male students and are exposed to a vertical sinusoidal vibration in the range of 2 to 20Hz at sitting and lying postures. Moreover, the subjective evaluation is conducted regarding the vibration sensation of parts of the body. The results are that (1) the whole body as a rigid body vibrates with the table by same amplitude and phase at 2Hz, (2) the vibrations of parts of the body become strong at 5Hz and 8Hz, and the vibration conditions of the parts are varied with the postures and subjects, (3) the feet and the head vibrate violently in the range of 11 to 20Hz, but the torso (abdomen and chest) decreased. Finally, it is clear that the transmission of vibration in human body is greatly influenced by the body characteristics as well as the postures of the subjects.